2020
DOI: 10.1155/2020/4710780
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Bioinformatic Analysis of the circRNA Expression in Migraine Patients

Abstract: Background. CircRNAs are noncoding RNA molecules that have recently been described and shown to regulate miRNA functionality. While recent studies have suggested such circRNAs to be associated with pain related diseases in humans, no comprehensive migraine-related circRNA profiles have been generated, and there is currently no clear understanding of whether they can serve as regulators of migraine pathology. Methods. We initially conducted a circRNA microarray analysis of the plasma of migraine patients and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…CircRNAs, a type of non-coding RNAs, can mediate the functions of diverse molecules including non-coding RNAs, mRNAs, DNA, and proteins. Thus, circRNAs play critical roles in tumor genesis and development, in sensitivity to radiation and chemotherapy, and in pain ( Wang et al, 2018 ; Kristensen et al, 2019 ; Zhang et al, 2019 ; Lin et al, 2020 ; Song et al, 2020 ; Zhang H. H. et al, 2020 ). In our present study, we found that 16 circRNAs in the DRG showed altered expression levels in response to treatment using PTX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs, a type of non-coding RNAs, can mediate the functions of diverse molecules including non-coding RNAs, mRNAs, DNA, and proteins. Thus, circRNAs play critical roles in tumor genesis and development, in sensitivity to radiation and chemotherapy, and in pain ( Wang et al, 2018 ; Kristensen et al, 2019 ; Zhang et al, 2019 ; Lin et al, 2020 ; Song et al, 2020 ; Zhang H. H. et al, 2020 ). In our present study, we found that 16 circRNAs in the DRG showed altered expression levels in response to treatment using PTX.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs, a type of non-coding RNAs, have been identified as miRNA sponges that regulate the expression and function of coding mRNAs, and are involved in various biological processes including pain (Wang et al, 2018;Lin et al, 2020;Song et al, 2020;Zhang H. H. et al, 2020). From our Bupivacaine (Bv)-induced neural apoptosis↑ ; diabetic peripheral neuropathy (Bali et al, 2021) 10.3389/fnmol.2022.990260 RNA-Seq data, 16 circRNAs were extracted as DEGs induced by treatment using PTX (Figure 3A and Table 5).…”
Section: Differentially Expressed Circrnas Induced By Treatment Using...mentioning
confidence: 99%
“…The lower the P-value is, the more significant the pathway. 16 The recommended P-value cutoff is 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Another possible epigenetic marker significant for migraine could be circRNA. Lin et al identified 794 and 1245 circRNAs, which were increased and decreased, respectively, in migraineurs compared to healthy controls [62]. The authors concluded that hsa_circRNA_103670, hsa_circRNA_103809, hsa_circRNA_000367, and hsa_circRNA_102413 may be closely related to the development of migraine.…”
Section: The Role Of Circrnas In Migraine Pathophysiologymentioning
confidence: 99%